1999
DOI: 10.1023/a:1024797014210
|View full text |Cite
|
Sign up to set email alerts
|

Divalproex in posttraumatic stress disorder: An open‐label clinical trial

Abstract: Posttraumatic stress disorder (PTSD) is characterized by intrusive, avoidance, and hyperarousal symptoms. This study was conducted to investigate the effectiveness of divalproex in reducing PTSD symptoms, depression, and anxiety in patients with PTSD. Sixteen patients with a DSM-IV diagnosis of PTSD at the Albuquerque VAMC outpatient PTSD treatment program received an open-label trial of divalproex. The patients were evaluated at baseline and at 8 weeks by a trained rater using the Clinician Administered PTSD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 14 publications
1
38
1
Order By: Relevance
“…These results suggest that divalproex sodium may be a useful adjunctive pharmacologic agent for managing patients with anger associated with PTSD who receive psychotherapy. These preliminary findings support those of other studies [17][18][19][20] that have demonstrated improvement in PTSD symptoms during open-label treatment with divalproex sodium across diverse populations of PTSD patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results suggest that divalproex sodium may be a useful adjunctive pharmacologic agent for managing patients with anger associated with PTSD who receive psychotherapy. These preliminary findings support those of other studies [17][18][19][20] that have demonstrated improvement in PTSD symptoms during open-label treatment with divalproex sodium across diverse populations of PTSD patients.…”
Section: Discussionsupporting
confidence: 89%
“…Notably, carbamazepine has been associated with improvement in flashbacks, nightmares, and reexperiencing (ie, intrusive thoughts), [15][16][17] and divalproex sodium has been reported to improve reexperiencing, hyperarousal/hyperreactivity, avoidance, and anger/ aggression. [17][18][19][20] Data from open trials suggest a role for other anticonvulsants, such as lamotrigine 21 or topiramate. 22 Because most reports have focused on combat-related PTSD in male military veterans, the generalizability of the findings to PTSD in civilian populations has not yet been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…The antiepileptic drug (AED) lamotrigine has also been used in a 12-week double-blind study of 15 patients, showing improvement on both re-experiencing and avoidance/ numbing symptoms compared to placebo patients . Another open label trial with 8 weeks of divalproex showed significant decrease of intrusion and hyperarousal symptoms, while no significant change was seen in avoidance/numbing symptoms [Clark et al, 1999]. Based upon anxiolytic reports of gabapentin in animal studies [de-Paris et al, 2000] and their ef ficacy in panic disorder [Pande et al, 2000], its first use in PTSD might be efficacious [Brannon et al, 2000].…”
Section: Anti-epileptics/antikindling Agentsmentioning
confidence: 99%
“…Davis et al, 2008). Nevertheless, valproic acid is sometimes used as an adjunctive agent, particularly among combat veterans with prominent hyperarousal symptoms (Fesler, 1991;Clark et al, 1999). Other anti-epileptic agents have been studied for use in chronic PTSD.…”
Section: Augmentationmentioning
confidence: 99%